Everything in the “right” place: multifocal transient ST segment elevation in patient with single coronary artery arising from the right Valsalva sinus - Suma, Sergio; Buffa, Claudia; Solinas, Emilia; Borrello, Bruno; Gaibazzi, Nicola; Gherli, Tiziano; Vignali, Luigi (Acta Biomedica Atenei Parmensis, 2019)
Single coronary artery (SCA) is a rare coronary anomaly that occurs with an incidence of 0.024%. We report the case of an 83-year-old woman with a Lipton’s type 3 SCA, which is the rarest anomaly within this group, occurring only in the 0.004% of general population.  The clinical presentation of this patient was chest pain at rest with multifocal transient ST segment elevation as a marker of multifocal ischemia secondary to severe three vessels coronary artery disease (CAD). This patient was proposed for coronary artery bypass grafting (CABG) with an excellent mid-term outcome.